SISWA DI ERA DIGITAL: BAGAIMANA TEKNOLOGI MENGUBAH KEPRIBADIAN REMAJA - Febriani, Aidilla Fitri; Faridah, Ayumi; Rachmaatillah, Tsalistiani; Mu'arifah, Alif (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
The rapid development of digital technology, especially through social media and various digital devices, has brought significant changes to the lives of adolescents today. This study aims to understand how digital technology influences the formation and transformation of adolescent personalities. By using a literature review as the research method, the results show that digital technology affects the psychological and social aspects of adolescents in complex ways. Although it provides ease of interaction and access to information, technology also presents new challenges related to identity, social skills, and emotional management. Social media, in particular, plays a role in shaping adolescents’ self-perception and has an impact on their psychological well-being. In addition, the presence of digital communication tools facilitates social interaction among adolescents, but also brings new risks related to psychological health. Therefore, guidance and counseling services are needed to help adolescents understand and manage the impact of digital technology on their personalities. Counselors can provide approaches that support adolescents in developing their identities and social skills in the digital era. Social skills, emotional regulation, and a supportive environment are also important factors for adolescent well-being. With good collaboration between schools, families, and communities, adolescents can adapt and develop optimally amid the rapid flow of digitalization, while being able to utilize technology wisely to maintain mental and social health.